Hereditas - Baumgartner, Stefan; Shi, Yongyong
For almost a century, Hereditas has published original cutting-edge research and reviews. As the Official journal of the Mendelian Society of Lund, the journal welcomes research from across all areas of genetics and genomics. Topics of interest include human and medical genetics, animal and plant genetics, microbial genetics, agriculture and bioinformatics. Articles covering novel viral sequences or the use of new technology and software in genomic research are also welcomed.